2018
DOI: 10.1051/e3sconf/20187301021
|View full text |Cite
|
Sign up to set email alerts
|

Fuel Oil from Municipal Plastic Waste through Pyrolysis with and without Natural Zeolite as Catalysts

Abstract: The main purpose of this work was the possibility to process the plastic waste into an alternative fuel oil through pyrolysis. This pyrolytic fuel can be utilized as an alternative fuel for cookstoves as a liquid petroleum gas (LPG)/kerosene substitute for the household. The pyrolysis was conducted in a design of a simple, inexpensive and easy to operate semi-batch reactors that be applied definitely in urban and rural communities. Two type of plastic wastes were pyrolyzed up to 480°C with and without natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
1
13
0
1
Order By: Relevance
“…Naturally occurring silica‐rich zeolites, such as clinoptilolite and mordenite, are studied as potential catalyst materials because they are readily available and inexpensive [99] . Natural zeolites in the protonated form have been used for PP, HDPE, LDPE, PS, PP/HDPE, EVA, and PET degradations and have shown moderate cracking ability and improved yields of liquid product, while also increasing char production [98,99,107,111,112,182–194] . However, catalyst efficiency has been strongly correlated to p/c ratio [191,192] .…”
Section: Heterogeneous Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…Naturally occurring silica‐rich zeolites, such as clinoptilolite and mordenite, are studied as potential catalyst materials because they are readily available and inexpensive [99] . Natural zeolites in the protonated form have been used for PP, HDPE, LDPE, PS, PP/HDPE, EVA, and PET degradations and have shown moderate cracking ability and improved yields of liquid product, while also increasing char production [98,99,107,111,112,182–194] . However, catalyst efficiency has been strongly correlated to p/c ratio [191,192] .…”
Section: Heterogeneous Catalystsmentioning
confidence: 99%
“…Natural zeolites in the protonated form have been used for PP, HDPE, LDPE, PS, PP/HDPE, EVA, and PET degradations and have shown moderate cracking ability and improved yields of liquid product, while also increasing char production [98,99,107,111,112,182–194] . However, catalyst efficiency has been strongly correlated to p/c ratio [191,192] . For example, when catalyzing polystyrene at a high p/c ratio at 450 °C, natural zeolite has been found to decrease liquid and gas production as compared to thermal degradation while significantly increasing char concentration [111,191] .…”
Section: Heterogeneous Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 , 6 However, according to previous research, there are some cases where the basic fuel properties of crude waste plastic oil were close to commercial gasoline and kerosene. 7 , 8 Essentially, the chemical compositions of liquid fuel from the pyrolysis process are affected by different types of plastic waste. The research established by Istoto et al showed that the chemical compositions of liquid fuel from high-density polyethylene (HDPE) and low-density polyethylene (LDPE) were analyzed by gas chromatography–mass spectrometry (GC-MS).…”
Section: Introductionmentioning
confidence: 99%
“…High fuel oil viscosity would cause incomplete combustion and lead to the formation of carbon deposits in the combustion vessel or burner. This parameter also affects the difficulty of ignition and pumping [23]. The addition of a catalyst into the process can result in advantages and better properties of the liquid fraction (lower heavy oil-waxes).…”
Section: Introductionmentioning
confidence: 99%